Digital Islam: A Hybrid Systematic Review and Bibliometric Analysis - Nurfazri, Muhammad; S. Truna, Dody; Haryanti, Erni; Sulaeman, Dedi (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to explore the development and conceptual direction of Digital Islam through a Systematic Literature Review and Bibliometric Analysis. Data were collected from Scopus (2020-2025) with an exclusive focus on the primary keyword “Digital Islam” to provide a more specific and in-depth perspective. Of the 561 articles collected, only four were included in the review analysis stage. The results indicate that academic interest in the study of Digital Islam remains relatively low; however, the topic is steadily increasing, suggesting that this field remains a significant and rapidly growing area of research. Geographically, the research is dominated by contributions from Indonesia, the United Arab Emirates, Germany, the United States, and Morocco. These findings demonstrate that countries with Muslim-majority populations do not solely dominate the issue of Digital Islam. In addition, Digital Islam, developed from four published studies, presents an integrative framework that links religious authority, digital media, identity, gender, economic transformation, and socio-cultural issues. Theoretically, this research contributes to the development of a conceptual foundation for future studies of Digital Islam. Practically, the results offer valuable insights for educators, policymakers, and religious institutions to navigate the ethical challenges and opportunities of the digital era